(untitled) (Revista Espinhaço, 2023)
Brazil stands out for having the greatest diversity of Neotropical mammals. This study conducted a review of the species checklist of small mammals (Didelphimorphia, Chiroptera, and Rodentia) recorded in the Espinhaço Range to expand and update the knowledge about local fauna. Occurrence records for small mammal species of the Espinhaço were obtained from indexed scientific papers published between 2008 and 2022 and a recent survey as part of the Long-Term Ecological Project - PELD Turfeiras da Serra do Espinhaço. The species were classified in relation to their national and global threat category. A total of 115 species were recorded (25 new records), including 20 species of marsupials, 43 of bats, and 52 of rodents, with six species classified as Endangered, eight as Vulnerable, and 13 as Data Deficient. We identified 40 endemic species, four of which were identified as restricted to the Espinhaço Range. The results of this review may provide support and guidance to expand and update the knowledge about the small mammal fauna of Espinhaço. However, further reviews and surveys in undersampled areas, such as the Espinhaço Range, are essential initiatives to define priority areas for conservation and management plans, particularly for endangered species.